Distortion Correction of Visante Optical Coherence Tomography Cornea Images. Issue 12 (December 2015) - Ramasubramanian, Viswanathan; Glasser, Adrian
ABSTRACT: Purpose: Quantitative biometry measurements from uncorrected anterior segment optical coherence tomography (AS-OCT) images are inaccurate because of spatial and optical distortions. Prior reported distortion correction equations for the Visante AS-OCT were not reproducible. The goal was to calculate the distortions and provide equations to correct corneal parameters for the Visante AS-OCT to get a central corneal radius of curvature from young and older subjects. Methods: Five contact lenses (CLs) of known front and back radii of curvature and central thickness were imaged using the Visante AS-OCT (Carl Zeiss, Dublin, CA). Contact lens surface coordinates from Visante images were identified and fitted with a circle using custom Matlab image analysis software. Spatial and optical distortions of the Visante image of the CL radii of curvature and thickness were calculated and corrected. Visante images were also captured from 24 younger (aged 21 to 36 years) and 30 older (aged 36 to 48 years) human subjects. Corneal radii of curvature and thickness measurements from these subjects were corrected, and intrasession and intersession repeatabilities of the corneal parameters were calculated. Results: Root mean square error of radius and power of the CL surfaces after distortion correction were 0.02 mm and 0.18D for the front and 0.011 mm and 0.11D for the back, respectively. Intraclass correlation coefficient for intrasession and intersession repeatability for all the corneal parameters from the human subjects was greater than 0.88 in both age groups. Conclusions: A distortion correction algorithm was developed for the Visante AS-OCT and applied to extract human corneal radius of curvature measurements. Abstract : Supplemental digital content is available in the text.